Psychosocial ethical aspects of AIDS. - Ross, M W (1989)
The psychosocial morbidity associated with HIV infection and responses to such infection may exceed morbidity associated with medical sequelae of such infection. This paper argues that negative judgements on those with HIV infection or in groups associated with such infection will cause avoidable psychological and social distress. Moral judgements made regarding HIV infection may also harm the common good by promoting conditions which may increase the spread of HIV infection. This paper examines these two lines of argument with regard to the ethical aspects of psychological bases of health care, clinical contact, public perceptions of AIDS and the comparative perspective. It is concluded that the psychosocial aspects of HIV infection impose ethical psychological, as well as medical, obligations to reduce harm and prevent the spread of infection.